Absence of virological and epidemiological evidence that SARS-CoV-2 poses COVID-19 risks from environmental fecal waste, wastewater and water exposures. (10th December 2021) - Sobsey, Mark D.
Abstract: This review considers evidence for infectious severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) presence and COVID-19 infection and illness resulting from exposure to environmental fecal wastes and waters. There is no documented evidence that (1) infectious, replication-capable SARS-CoV-2 is present in environmental fecal wastes, wastewater or water, and (2) well-documented epidemiological evidence of COVID-19 infection, illness or death has never been reported for these exposure media. COVID-19 is transmitted mainly by direct personal contact and respiratory secretions as airborne droplets and aerosols, and less so by respiratory-secreted fomites via contact (touch) exposures. While SARS-CoV-2 often infects the gastrointestinal tract of infected people, its presence as infectious, replication-capable virus in environmental fecal wastes and waters has never been documented. There is only rare and unquantified evidence of infectious, replication-capable SARS-CoV-2 in recently shed feces of COVID-19 hospital patients. The human infectivity dose–response relationship of SARS-CoV-2 is unknown, thereby making it impossible to estimate evidence-based quantitative health effects assessments by quantitative microbial risk assessment methods requiring both known exposure assessment and health effects assessment data. The World Health Organization, Water Environment Federation, US Centers for Disease Control and Prevention and others do not consider environmental fecal wastes and waters as sources of exposure to infectious SARS-CoV-2 causing COVID-19 infection and illness. HIGHLIGHTS: No infectious severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has been found in fecal wastes or waters. There is no epidemiological evidence of COVID-19 infection, illness or death from exposures via environmental fecal wastes or waters. Health risk assessments for COVID-19 by quantitative microbial risk assessment are not possible. There is no evidence of infectious SARS-CoV-2 in fecal wastes and waters or COVID-19 infection, illness and death attributable to such exposure media. Additional and coordinated efforts are recommended to further seek infectious, replication-capable SARS-CoV-2 in environmental fecal wastes and water using state-of-the-science methods. Graphical Abstract